2016
DOI: 10.1161/jaha.115.003010
|View full text |Cite
|
Sign up to set email alerts
|

Posttraumatic Stress Disorder Is Associated With Worse Endothelial Function Among Veterans

Abstract: Background--Current research in behavioral cardiology reveals a significant association between posttraumatic stress disorder (PTSD) and increased risk for cardiovascular disease and mortality; however, the underlying mechanisms remain poorly understood. We hypothesized that patients with PTSD would exhibit endothelial dysfunction, a potential mechanism involved in the development and progression of cardiovascular disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(45 citation statements)
references
References 47 publications
(73 reference statements)
0
44
0
1
Order By: Relevance
“…It is now well-established that PTSD is independently associated with increased risk for coronary artery disease and related mortality (Edmondson & Cohen 2013, Edmondson et al 2013). Moreover, among veterans treated in an outpatient clinic, those with PTSD had worse indicators of endothelial function (Grenon et al 2016), which might have contributed to the early onset and progression of CVD in this population. Similarly, PTSD within the Danish general population was associated with higher rates of myocardial infarction, ischaemic stroke and venous thromboembolism, irrespective of gender (Gradus et al 2015).…”
Section: Posttraumatic Stress Disorder: Emerging Risk Factors For Carmentioning
confidence: 99%
“…It is now well-established that PTSD is independently associated with increased risk for coronary artery disease and related mortality (Edmondson & Cohen 2013, Edmondson et al 2013). Moreover, among veterans treated in an outpatient clinic, those with PTSD had worse indicators of endothelial function (Grenon et al 2016), which might have contributed to the early onset and progression of CVD in this population. Similarly, PTSD within the Danish general population was associated with higher rates of myocardial infarction, ischaemic stroke and venous thromboembolism, irrespective of gender (Gradus et al 2015).…”
Section: Posttraumatic Stress Disorder: Emerging Risk Factors For Carmentioning
confidence: 99%
“…The general pattern of results across that line of research provides support for associations between PTSD and C-reactive protein [74, 75, 76•], TNFα [76•, 77], IL-6 [77], and IL-1β [77]. Additionally, a growing body of evidence suggests that PTSD is cross-sectionally associated with impaired endothelial functioning as measured by circulating markers of endothelial cell integrity [76•], and direct observation of nitric oxide-related vascular reactivity in the brachial artery [78]. There is also preliminary evidence that PTSD predicts increasing endothelial cell dysfunction over time [76•].…”
Section: Traumatic Stress and Inflammation And Immune Responsementioning
confidence: 99%
“…Specifically, robust associations between estimated white blood cell counts and accelerated DNAm age have emerged across studies, such as a negative relationship between CD4 T-cell counts and accelerated Hannum DNAm [55, 60••, 6162]. There is also preliminary evidence for an association between Horvath epigenetic age acceleration (adjusted for white blood cell counts) and increased C-reactive protein as well as between Hannum epigenetic age acceleration (in an index combined with white blood cell counts, see below) and increased C-reactive protein [78]. However, the interpretation of these associations is not yet clear.…”
Section: Potential Mechanisms Linking Traumatic Stress To Acceleratedmentioning
confidence: 99%
“…Multiple large epidemiological studies have demonstrated that PTSD is independently associated with a significantly greater risk for developing hypertension, other cardiovascular diseases such as coronary artery disease, and mortality (8,32). Although the mechanisms leading to increased cardiovascular disease risk are not fully understood, recent evidence suggests chronically heightened sympathetic nervous system (SNS) activity and reactivity (24,44) in patients with PTSD that is mediated by altered arterial baroreflex sensitivity (BRS) (44). SNS overactivity has a major role in causing and sustaining hypertension (21) and contributes to the development of heart failure (31), arrhythmias (22), and atherogenesis (17).…”
Section: Introductionmentioning
confidence: 99%